2014
DOI: 10.1371/journal.pone.0100818
|View full text |Cite
|
Sign up to set email alerts
|

Local Injection of Deferoxamine Improves Neovascularization in Ischemic Diabetic Random Flap by Increasing HIF-1α and VEGF Expression

Abstract: BackgroundAlthough the systemic administration of deferoxamine (DFO) is protective in experimental models of normal ischemic flap and diabetic wound, its effect on diabetic flap ischemia using a local injection remains unknown.ObjectiveTo explore the feasibility of local injection of DFO to improve the survival of ischemic random skin flaps in streptozotocin (STZ)-induced diabetic mice.MethodsIschemic random skin flaps were made in 125 mice. Animals were divided into the DFO-treated (n = 20), PBS-treated (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 34 publications
(51 reference statements)
1
37
1
Order By: Relevance
“…Wang et al . showed that local injections of DFO enhanced healing in diabetic skin flaps in mice, similar to non-diabetic animals, through an increased production of HIF-1α and VEGF20. Hou et al .…”
Section: Discussionmentioning
confidence: 98%
“…Wang et al . showed that local injections of DFO enhanced healing in diabetic skin flaps in mice, similar to non-diabetic animals, through an increased production of HIF-1α and VEGF20. Hou et al .…”
Section: Discussionmentioning
confidence: 98%
“…DFO prevented the methylglyoxal modification of p300, which has been shown to impact negatively on the heterodimerization of the two HIF‐1 subunits . Additionally, local injection of DFO into ischaemic flaps of diabetic mice resulted in wound healing enhancement and prevention of flap necrosis by increasing HIF‐1α and VEGF expression, endothelial cell recruitment and neovascularization …”
mentioning
confidence: 99%
“…16 Briefly, 500 ml of nifedipine solution (10 mmol/L) in methanol was placed in a glass beaker and then exposed to a halogen light (500W, Kodak Ektagraphic III Projector, Kodak, Rochester, NY) with constant stirring. The eluent corresponding to newly observed peaks was collected and evaporated for determination of its structure by 1 H-NMR, 13 C-NMR, IR, and ESI-MS. After 18 hours of irradiation under our experimental conditions, nifedipine had been completely converted to NO-NIF with a purity of more than 99%.…”
Section: Preparation Of No-nifmentioning
confidence: 99%
“…Actually, use of superoxide dismutase (SOD), an endogenous scavenger of the superoxide radical, increased flap survival . Other antioxidative drugs have also successfully been applied to protect against flap necrosis in animal models …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation